Enhancing gain for uwb antennas using fss: A systematic review - Al-Gburi, A.J.A. (MDPI, 2021)
This review paper combs through reports that have enhanced antenna gain for ultra-wideband (UWB) frequencies using frequency-selective surface (FSS) techniques. The FSS techniques found across the research landscape were mapped onto a taxonomy in order to determine the most effective method for improving antenna gain. Additionally, this study looked into the motivation behind using FSS as a reflector in UWB frequencies to obtain directional radiation. The FSS suits multiple applications due to its exceptional ability to minimize power loss in undesired transmission areas in the antenna, as well as to hinder the interference that may occur from undesirable and wasted radiation. An efficient way to obtain constant gain over a wide range of frequencies is also elaborated in this paper. Essentially, this paper offers viable prescription to enhance antenna gain for UWB applications. Methods: A comprehensive study was performed using several imminent keywords, such as âhigh gain using FSSâ, âgain enhancement using FSSâ, âhigh gain UWB antennasâ, and âgain enhancement of UWB antennasâ, in different modifications to retrieve all related articles from three primary engines: Web of Science (WoS), IEEE Xplore, and Science Direct. Results: The 41 papers identified after a comprehensive literature review were classified into two categories. The FSS single-and multi-layer reflectors were reported in 25 and 16 papers, respectively. New direction: An effective method is proposed for FSS miniaturization and for obtaining constant gain over UWB frequencies while maintaining the return loss at â10 dB. Conclusion: The use of FSS is indeed effective and viable for gain enhancement in UWB antennas. This systematic review unravels a vast range of opportunities for researchers to bridge the identified gaps. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.